Potential to reduce antibiotic use in secondary care: Single-centre process audit of prescription duration using NICE guidance for common infections. Issue 1 (2021) - Powell, Neil; Stephens, Jennie; Rule, Rory; Phillips, Ryan; Morphew, Megan; Garry, Emma
No abstract available